Decoding bacteriophage P22 assembly: identification of two charged residues in scaffolding protein responsible for coat protein interaction - Cortines, Juliana R. (2011)
Proper assembly of viruses must occur through specific interactions between capsid proteins. Many double-stranded DNA viruses and bacteriophages require internal scaffolding proteins to assemble their coat proteins into icosahedral capsids. The 303 amino acid bacteriophage P22 scaffolding protein is mostly helical, and its C-terminal helix-turn-helix (HTH) domain binds to the coat protein during virion assembly, directing the formation of an intermediate structure called the procapsid. The interaction between coat and scaffolding protein HTH domain is electrostatic, but the amino acids that form the protein-protein interface have yet to be described. In the present study, we used alanine scanning mutagenesis of charged surface residues of the C-terminal HTH domain of scaffolding protein. We have determined that P22 scaffolding protein residues R293 and K296 are crucial for binding to coat protein and that the neighboring charges are not essential but do modulate the affinity between the two proteins.